The Witch Bubble. Paco’s Adventures - Arencibia Pardo, Francisco Raúl; Martínez Melo, Luciana (Sello Editorial Unipamplona, 2025)
A fantasy and storybook for children ages 8 to 12. The Witch Bubble "Paco’s Adventures" is a fascinating story you can immerse yourself in, filled with great adventures, anecdotes, and moments.